Ethnographic Drawings in the Vilnius University Library, Created During the 1864–1867 Expeditions Arranged by Ivan Kornilov - Girininkaitė, Veronika (Literatūra, 2025)
A collection of mid-19th-century ethnographic drawings is stored at Vilnius University Library. These drawings were created from nature in the territories of modern Lithuania and Belarus. Some drawings are unsigned, whereas other drawings hold signatures. Older library records indicate that these were the drawings created by the school art teachers between 1864 and 1867, during expeditions arranged by Ivan Kornilov, the curator of the Vilnius Educational District and head of Vilnius Public Library. Many of them were exhibited in the Vilnius Public Library exhibition in 1911. Although the entirety of Kornilov’s activities were politically charged, and the main aim of the expeditions Kornilov arranged was to discover and demonstrate the ancient substratum of the Russian culture in the occupied territories, the drawings in question appear to be politically neutral, merely documenting ethnographic details. The drawings of Dmitrij Strukov were added to this collection by mistake, because this artist’s work was commissioned not by the head of Vilnius Public Library. Even without considering the valuable drawings of Strukov, the rest of the works are of great interest to researchers. The article aims to reconstruct the circumstances of the creation of these drawings.
Keywords: Vilnius Public Library; Ivan Kornilov; Dmitrij Strukov; thnographic drawings; Russification